KEBEBASAN HAKIM DAN KEPASTIAN HUKUM DALAM MENANGANI PERKARA PIDANA DI INDONESIA - Vivi Ariyanti (IAIN Syekh Nurjati Cirebon, 2019)
The nature of law rests on the idea of justice and moral strength. Justice and injustice according to a law will be measured and judged by a morality that refers to human dignity. Judges participate in the formation of law, not objectively like the law created by legislators, but judges apply abstract text of the law to concrete legal events. This paper discusses the role of judges in ensuring legal certainty and justice in society, especially in handling criminal cases. This study uses a normative and philosophical analysis of the application of the principle of judicial independence in the resolution of criminal cases in the Indonesian criminal justice system. This paper concludes that judges as the spearhead of the enforcement of justice need to have the same perception about the application of the principle of judicial independence in carrying out criminal offenses. It is hoped that the uniformity of mindset in applying these rules from judges throughout Indonesia is no longer the case with the disparity in the conviction, which results in public dissatisfaction with the judge's decision.